Local knowledge spillovers and the effects of related and unrelated variety on the novelty of innovation - Mascarini, Suelene; Garcia, Renato; Quatraro, Francesco (Regional studies, 2023)
Knowledge spillovers have been identified as a factor affecting the unequal distribution of innovation in space. In this paper we aim to understand how territorial factors shape the novelty degree of innovations. Thus, we perform an empirical analysis that relates territorial factors to innovative performance at the firm level. Our results show that local knowledge spillovers from research and development expenditures are positively associated with upper-level innovation, while local knowledge spillovers from total innovation expenditures are not related to the degree of novelty of innovation. Furthermore, the impacts on innovation are also moderated by related and unrelated varieties since firms in regions with higher regional-related variety are less likely to generate upper-level innovation.